Relating Competitive Golfers' Perceived Emotions and Performance. Issue 4 (August 2021) - Lundkvist, Erik; Gustafsson, Henrik; Björklund, Gunilla; Davis, Paul; Ivarsson, Andreas
The present study examined relationships between golfers' self-perceived emotions (e.g., irritability, nervousness, tension), task-oriented coping, perceived control, and performance during a golf competition. We implemented a process-oriented golf analysis in which competitors rated these variables hole-by-hole in a competitive golf round. Within a two-level Bayesian multivariate autoregressive model, we showed that (a) within persons, emotions and task-oriented coping were reactions that stemmed from performance on the previous hole; and (b) between persons, player skill level predicted both better scores and the ability to limit the influence of negative affect on performance. These findings highlight the complex nature of the relationship between emotions and performance. Future studies might use a similarly ecologically valid research design to more precisely measure aspects of time and potentially moderating effects of player skill level and personality. An increased understanding of the dynamic relationship between emotions and performance can promote the development of effective psychological interventions for optimal performance outcomes.